The Principle of Subsidiarity as a Valuable Benchmark in the Regulation of Economic Relations - Kondratienė, Virginija (Annales. Etyka w Życiu Gospodarczym, 2014)
The principle of subsidiarity can be an effective tool for adjusting economic systems and establishing the social rule-of-law concept in public organisation. In considering the usability of the principle of subsidiarity, the following aspects thereof are discussed: the role in the development of the European social model; employment in determining limits for the powers of the public and private sectors; the application in the market and planned economy systems; and the social justice function in the development of a social welfare state. The principle of subsidiarity as an instrument for individuals’ interests, balancing and adjusting in the regulation of economic systems, helps to establish the relative sizes of public policy and the market, as subsidiarity can help ensure a more equitable distribution of public goods while guaranteeing the maintenance of the creative potency of operators and minimal satisfaction of vital needs of individuals unable to contribute to the production of goods. It amounts to a constitutional measure determining the balance of productive and protective state, thus ensuring the stability of the state organisation. In the concept of a social rule-of-law state, subsidiarity draws clear limits to the state’s powers, institutionally bringing together efforts of all members of the community to achieve welfare in the state.